2007
DOI: 10.1128/jb.01068-07
|View full text |Cite
|
Sign up to set email alerts
|

Array-Based Genomic Comparative Hybridization Analysis of Field Strains ofMycoplasma hyopneumoniae

Abstract: Mycoplasma hyopneumoniae is the causative agent of porcine enzootic pneumonia and a major factor in the porcine respiratory disease complex. A clear understanding of the mechanisms of pathogenesis does not exist, although it is clear that M. hyopneumoniae adheres to porcine ciliated epithelium by action of a protein called P97. Previous studies have shown variation in the gene encoding the P97 cilium adhesin in different strains of M. hyopneumoniae, but the extent of genetic variation among field strains acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…M. hyopneumoniae strain 232 (26) was used throughout this study unless stated otherwise. Additional strains of M. hyopneumoniae were isolated from various locations, including the laboratory-adapted strain J (25) and field strains OMZ407 (25), Hillcrest (isolated from New South Wales, Australia in 2003 and provided by Graeme Eamens at the Elizabeth Macarthur Agricultural Institute, New South Wales, Australia), 95MP1509 (27), 00MP1301 (27), C1735/2 (25), and 2-22421 (provided by J. Forbes-Faulkner, Oonoonba Veterinary Laboratory, Queensland, Australia). Escherichia coli TOP10 or BL21 star (DE3) (Invitrogen) were grown on LuriaBertani agar plates or cultured in Luria-Bertani medium with shaking at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…M. hyopneumoniae strain 232 (26) was used throughout this study unless stated otherwise. Additional strains of M. hyopneumoniae were isolated from various locations, including the laboratory-adapted strain J (25) and field strains OMZ407 (25), Hillcrest (isolated from New South Wales, Australia in 2003 and provided by Graeme Eamens at the Elizabeth Macarthur Agricultural Institute, New South Wales, Australia), 95MP1509 (27), 00MP1301 (27), C1735/2 (25), and 2-22421 (provided by J. Forbes-Faulkner, Oonoonba Veterinary Laboratory, Queensland, Australia). Escherichia coli TOP10 or BL21 star (DE3) (Invitrogen) were grown on LuriaBertani agar plates or cultured in Luria-Bertani medium with shaking at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…One recent study has shown a considerable amount of genetic diversity among field isolates (12). To improve the diagnostic ability to detect field isolates of M. hyopneumoniae, the two real-time PCR assays developed for mhp165 and mhp183 were multiplexed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of PCR assays have been developed and reported to be both sensitive and specific for M. hyopneumoniae (4,6,11,19,20,22,24,26). As a result, this technique is now among the most widely used for detection of M. hyopneumoniae in pigs.While the development of PCR assays has greatly enhanced our ability to detect M. hyopneumoniae, the genetic variability of the organism (1,5,12,14,15,21) can affect detection by PCR. It is not known what effect this heterogeneity has on the sensitivities of the different assays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasmas have small genomes (580–1300 kb) [3, 4], and genetic diversity might be one solution to adapt to the adverse environment of the host [5, 6]. Many regions in the genome of M. hyopneumoniae related to adherence in the host contain variable number of tandem repeats (VNTRs).…”
Section: Introductionmentioning
confidence: 99%